Effect of the Extract of Dayak Onions (Eleutherine palmifolia) on the Sperm Quality of Mice (Mus musculus) Induced with Monosodium Glutamate - Rahmatullah, Aldin Akbar; Sugihartuti, Rahmi; Susilowati, Suherni; Hamid, Iwan Sahrial; Suprayogi, Tri Wahyu; Rachmawati, Kadek; Safitri, Erma; Mustofa, Imam; Mulyati, Sri (Media Kedokteran Hewan, 2024)
This study aims to determine the effect of the extract of Dayak onions (Eleutherine palmifolia) on the motility, viability, and concentration of spermatozoa in mice (Mus musculus) induced with monosodium glutamate (MSG). This study involved 25 male mice aged 11 weeks and weighing approximately 20 g. The mice were divided into five groups, namely C- (CMC-Na 0.5%), C+ (4 mg/g BW of MSG), T1 (4 mg/g BW of MSG and 30 mg/kg BW of Dayak onion extract), T2 (4 mg/g BW of MSG and 60 mg/kg BW of Dayak onion extract), and T3 (4 mg/g BW of MSG and 120 mg/kg BW of Dayak onion extract). All treatments were administered for 52 days. The results showed no significant differences in the motility and concentration of spermatozoa between the C- (81.50 ± 4.18; 7.21 ± 0.37) and T3 (77 ± 2.74; 7.04 ± 0.13) groups (p < 0.05). In addition, the results showed significant differences in the viability of spermatozoa between the C- (83.30 ± 3.40) and T3 (77.20 ± 4.06) groups. Therefore, it can be concluded that the administration of Dayak onion extracts orally to mice induced with MSG can maintain the motility, viability, and concentration of spermatozoa.